Um analisador fluxo-batelada baseado em imagem digital para determinação de Al(III) e Cr(VI) em águas - Andrade, Stéfani Iury Evangelista de (2012)
This study proposes a digital image-based flow-batch analyzer (DIB-FBA) for the determination of Al(III) and Cr(VI) in waters. The proposed DIB-FBA uses a webcam with CCD sensor for acquisition of the images generated according to the RGB (Red-Green-Blue) colour system. The method for determination of Al(III) is based on reaction of this ion with quercetin and cetyltrimethylammonium bromide, yielding a yellow complex with maximum absorption at 428 nm. Chromium(VI) determination is accomplished by reaction of this ion with 1,5-diphenylcarbazide, whose product is a violet complex with maximum absorption at 548 nm. All calibration solutions were prepared in-line, and all analytical processes completed by simply changing the operational parameters in the DIB-FBA control software. The linear response ranges from 10 to 600 μg L−1 for Al (III) and from 10 to 300 μg L−1 for Cr (VI). Linear models for analytical curves were validated using ANOVA, F-test for lack of fit and residual plots. The limits of detection and sampling rates were estimated as 3,97 μg L−1 and 137 h−1, for Al(III) and 3,40 μg L−1 and 134 h−1, for Cr(VI), respectively. DIB-FBA performance was compared with the reference methods for determination of both analytes, and no statistically significant difference was observed between results by applying the paired t-test at a 95% confidence level.